The Impact of Decentralized Finance (DeFi) on Traditional Banking Systems: A Novel Approach - Hadi, Syukri; Renaldo, Nicholas; Purnama, Intan; Veronica, Kristy; Musa, Sulaiman (International Conference on Business Management and Accounting, 2023)
This research explores the transformative impact of Decentralized Finance (DeFi) on traditional banking systems. DeFi, leveraging blockchain technology and smart contracts, has emerged as a significant disruptor in the financial industry by offering decentralized, transparent, and accessible financial services. This study aims to assess how DeFi challenges conventional banking models and the implications for the future of financial services. Through a mixed-methods approach, combining quantitative analysis of financial data and qualitative insights from industry experts, this research identifies key components of DeFi and examines its effects on traditional banking operations, customer experiences, and financial stability. The findings reveal a significant increase in DeFi transaction volumes and user engagement, accompanied by a reduction in certain traditional banking activities. While DeFi offers benefits such as lower transaction costs and enhanced accessibility, it also introduces challenges related to security, regulatory uncertainty, and market volatility. The study concludes that DeFi presents both opportunities and risks for traditional banking systems. To remain competitive, traditional banks may need to adopt blockchain technologies and explore strategic partnerships with DeFi platforms. Policymakers are advised to develop clear regulatory frameworks to manage associated risks while fostering innovation. This research provides valuable insights for financial institutions, regulators, and investors navigating the evolving landscape of financial services.